Comparison of Effects of Early Onset Depression and Late-Life Depression on Human Body - Asima Farooq, Sajawal Mir, Adeeb Ali, Muhammad Shuaib, Sumaiya Zulfiqar, Ali Arif, (Pakistan Journal of Medical & Health Sciences, 2022)
Late-life depression is considered as one of the features of older age instead of a treatable disease. This under recognition of this major disorder leads to multiple visits of patients to different medical consultants with different clinical presentations. This research aimed to find out the relevance of age of onset of depression with its serious life-threatening output like brain hemorrhage, suicide etc. Methods: Then if divide it according to its classifications, there will be two types of depression, first one is early-onset depression that happens before 60 years of age and second one is late-life depression that occurs in elderly 60 years of age or above. Age of onset matters alot while making diagnosis or treating depression because of the differences in treatment response and complications. Depression is directly linked with brain and start effecting whole body including. As the day’s passes, it effects more our brain and body as compared to previous day. 196 patients are taken as sample and divide them into different groups according to early and late life depression. Results: After the research, according to the results that are generated as patients with late life depression show more harmful effects and leads to brain hemorrhage as compared to those who was diagnosed during early-onset of depression. Conclusion: It is concluded that these hemorrhage and nervous disorder does not occur with early onset of depression but with late onset depression.